MAKNA REGULASI DIRI DALAM PENGALAMAN AGEN PEMULIHAN PROGRAM INTERVENSI BERBASIS MASYARAKAT: STUDI FENOMENOLOGI - Aisya Fadhila; Heri Ismanto; Padmi Yulianti (IKIP Siliwangi, 2026)
Drug abuse in Indonesia demands empowerment-based handling strategies through the Community-Based Intervention (IBM) Program. Recovery agents face complex challenges, requiring strong self-regulation to maintain work effectiveness and psychological resilience. This study explores the meaning of self-regulation within the lived experiences of recovery agents using a phenomenological approach. Three participants were purposively selected from Gayamsari Sub-district, Semarang City, with at least one year of active involvement and direct mentoring experience. Data were collected through semi-structured in-depth interviews and analyzed using phenomenological analysis supported by NVivo. The findings reveal three integrated dimensions of self-regulation: metacognition, motivation, and behavior. Recovery agents demonstrate goal setting, action evaluation, internalization of altruistic values, and adaptive strategies. Collaborative support from the National Narcotics Agency (BNN) and fellow agents strengthens individual self-regulation capacity. This study contributes theoretically to understanding self-regulation in social work and offers practical implications for developing holistic training and sustained support systems.